The spectrum of neutrophilic dermatoses associated with monoclonal gammopathy: Association with IgA isotype and inflammatory profile - Szalat, Raphael; Monsel, Gentiane; Le Goff, Wilfried; Battistella, Maxime; Bengouffa, Djaouida; Schlageter, Marie-Helene; Bouaziz, Jean-David; Arnulf, Bertrand; Vignon, Marguerite; Lesnik, Philippe; Saussine, Anne; Malphettes, Marion; et al. (Journal of the American Academy of Dermatology, 2015)
Neutrophilic dermatoses refer to a group of cutaneous inflammatory disorders characterized by neutrophilic infiltration of the skin. Neutrophilic dermatoses have been reported in association with various conditions including autoimmune diseases, inflammatory bowel diseases, and neoplasia. In the later condition, myeloproliferative disorders and monoclonal gammopathy (monoclonal immunoglobulin [MIg]) are the most frequent. Only few data are available in case of neutrophilic dermatoses associated with MIg regarding the pathophysiology and the clinical outcome. We sought to gain further insight into clinical and biological aspects of neutrophilic dermatoses associated with MIg. We report a retrospective series of 26 patients with neutrophilic dermatoses associated with MIg focusing on clinical and biological aspects, with a study of a large panel of cytokines, chemokines, and adhesion molecules. This study reveals an association between MIg IgA isotype and neutrophilic dermatoses, and a specific inflammatory pattern including elevated interleukin 6, vascular endothelial growth factor, monocyte chemotactic protein-1, epidermal growth factor, and intercellular adhesion molecule-1. This is a retrospective study from a single institution with a limited number of participants. Our data highlight a strong association between IgA isotype and neutrophilic dermatoses, and the existence of a specific inflammatory profile involving several molecules.